Fusidic acid/tea-tree oil nanoemulsions : a potentially safe and effective anti MRSA/MSSA topical agent for chronic wound healing - Ahmed Yaseen; Mohammed Ghareeb, Mowafaq; Dania F. Alsaffar; Thaigarajan Parumasivam; Toh, Seok-Ming; Amirah Mohd Gazzali (Penerbit Universiti Kebangsaan Malaysia, 2022)
Fusidic acid (FA) is clinically used as an antibacterial agent for the treatment of Gram-positive bacterial infections. It interferes with bacterial protein synthesis, specifically by preventing the translocation of the elongation factor G on the ribosome. In the present work, oil-in-water nanoemulsion (NE) was developed as a carrier for the transdermal delivery of FA. Different oils, surfactants and co-surfactants were screened. The solubility of FA, the emulsifying capacity of the surfactants and phase diagrams for each oil and surfactant mix were constructed. From the analysis, eight stable NE formulations were chosen, and their physicochemical properties were further evaluated. The antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-sensitive Staphylococcus aureus (MSSA) were also evaluated, and cytotoxicity was conducted on HS-27 cell line to determine the safety of the formula. It was found that the NE produced from tea tree oil has the most optimal stability with promising antibacterial activity against MRSA as compared to a commercially available product. The safety profile of the NE was also comparable to the commercial product; thus, the formulated FA-NE is promising for clinical use.